Gatunki mowy czy gatunki tekstu z połowy XVIII wieku w tekstach literackich Elżbiety Drużbackiej 1 . Propozycja metodologiczna - Rittel, Teodozja (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The author of the article aims to discuss linguistic and genre features that distinguish literary texts of the prominent poet of the King Augustus III times - Elżbieta Drużbacka. The linguistic analysis of fairy-tales, fables, epigrams, and laments is carried out on the basis of lexicons of the Polish language.